2019
DOI: 10.1177/1473325019871607
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multi-dimensionality of permanence and stability: Emotions, experiences and temporality in young people’s discourses about long-term foster care in Ireland

Abstract: This paper focuses on qualitative findings on how young people in long-term foster care in Ireland 1 interpret permanence and stability. We focus principally on subjective and relational permanence, emphasising the significance of these concepts for social work, while extending some conceptual approaches to permanence. Importantly, findings from this study highlight conceptual gaps in how permanence and stability are conceptualised in research and we outline an approach which more fully embraces the multidimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The fundamental aim of the child welfare system is to ensure permanency of care (Department for Education, 2016a). Permanency has been conceptualised as both a subjective and objective phenomenon, shaped by young people's relationships, identity and belonging in a stable family context over time (Moran et al, 2020). This is frequently measured as the numbers of placements, relationship breakdowns and school moves.…”
Section: Stability and Permanencementioning
confidence: 99%
“…The fundamental aim of the child welfare system is to ensure permanency of care (Department for Education, 2016a). Permanency has been conceptualised as both a subjective and objective phenomenon, shaped by young people's relationships, identity and belonging in a stable family context over time (Moran et al, 2020). This is frequently measured as the numbers of placements, relationship breakdowns and school moves.…”
Section: Stability and Permanencementioning
confidence: 99%
“…There is no way of knowing now if, in the long term, the increased adoption of online platforms becomes an established trend, or how the pandemic might change biographical research in other ways. For now, we can only testify how novel and creative biographical research is ( Caetano and Nico, 2019 ; Moran et al, 2019 ), enabling us to adapt methodological toolkits to understand biographies in new ways in increasingly complex realities.…”
Section: Which Biographical Research?mentioning
confidence: 99%
“…Their research showed the importance of emotional bonds with birth parents in affecting social relationships later in life. In their qualitative study focused on permanency and stability for young people in care, Moran et al (2019) found that young people re-negotiated emotional bonds with their birth families, and emotions played a central part in understanding permanence and stability. In their study, some young people felt a sense of abandonment and anger towards birth parents, while others felt "torn" between birth parents and foster carers.…”
Section: The Emotional Dimension In Family Relationshipsmentioning
confidence: 99%